O direito ao desenvolvimento como concretizador do princípio da dignidade da pessoa humana - Ishikawa, Lauro (2008)
The dignity of the human person is the foundation and guarantee national development is fundamental goal of the Federative Republic of Brazil, as provided in Title I of the Federal Constitution of 1988. As the international texts on human rights the right to development is viewed as a human right consists of civil, political, economic, social and cultural. These rights form the catalogue of fundamental rights and, being inseparable, must ensure the minimum existential to everybody. As a fundamental right, the right to development, including those rights and guarantees arising from international treaties that the Brazil is party, must have immediate application, be put director element of the principle of human dignity